2015
DOI: 10.1038/nsmb.2959
|View full text |Cite|
|
Sign up to set email alerts
|

Exon-intron circular RNAs regulate transcription in the nucleus

Abstract: Noncoding RNAs (ncRNAs) have numerous roles in development and disease, and one of the prominent roles is to regulate gene expression. A vast number of circular RNAs (circRNAs) have been identified, and some have been shown to function as microRNA sponges in animal cells. Here, we report a class of circRNAs associated with RNA polymerase II in human cells. In these circRNAs, exons are circularized with introns 'retained' between exons; we term them exon-intron circRNAs or EIciRNAs. EIciRNAs predominantly local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
2,266
5
8

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,403 publications
(2,302 citation statements)
references
References 50 publications
23
2,266
5
8
Order By: Relevance
“…A recent study suggested that a subclass of circRNAs, exon-intron circRNAs (EIciRNAs), interact with the U1 snRNP and promote the transcription of their parental genes. 13 Despite the progress made so far, the number of functionally characterized circRNAs remains very low. Thousands of cytoplasmic circRNAs have been identified, with most of them having only 1 or 2 binding sites for a particular miRNA, which limits their potential regulatory potency as miRNA "sponges".…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that a subclass of circRNAs, exon-intron circRNAs (EIciRNAs), interact with the U1 snRNP and promote the transcription of their parental genes. 13 Despite the progress made so far, the number of functionally characterized circRNAs remains very low. Thousands of cytoplasmic circRNAs have been identified, with most of them having only 1 or 2 binding sites for a particular miRNA, which limits their potential regulatory potency as miRNA "sponges".…”
Section: Introductionmentioning
confidence: 99%
“…This view has however dramatically changed due to the fact that with the development of deep sequencing and bioinformatic tools a large number of circRNAs have been discovered in mammalian and other cells. [1][2][3][4][5]7 Strikingly, often circRNA is even the more abundant isoform than mRNA. 2,12,13 Due to their covalently closed ring structure, circRNAs have a higher stability in the cellular environment as compared with their linear counterparts, implying that possible functions of circRNA may be associated with the longer life time of these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, circRNAs can be formed from introns (hence termed circular intronic RNA (ciRNA), 6 or from exons with introns retained between the exons (termed exon-intron circRNA (IEciRNA). 7 However, the vast majority of circRNAs apparently is transcribed and spliced from exons of protein and noncoding genes. 1,10,11 Initially discovered as ubiquitous molecules in mice and human cells, those circRNAs were subsequently found as abundant, conserved and stable species in all eukaryotes studied today.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations